Capturing the amplitude and phase profile of the vortex beam based on coherent detection - Zhao, Shengmei; Qiao, Quanqing; Wang, Le (Frontiers in Physics, 2022)
In this paper, we propose a scheme to capture the amplitude and phase profile of the orbital angular momentum (OAM) beam based on coherent detection. In the scheme, the OAM beam to be measured is interfered with a local plain wave which is prepared at the receiver, and two Charge-coupled Devices (CCDs) are used to record the constructive and destructive interference patterns, respectively. By setting the phase of the plain wave to π/2 and π, one can extract the amplitude and phase profile of the OAM beam from the two interference patterns. We verify the feasibility of the scheme by the simulation and experiments. The results show that both amplitude and phase profiles of single OAM and OAM superposition modes can be captured by using the proposed scheme, and the proposed scheme has strong robustness even under the presence of atmospheric turbulence.